2006
DOI: 10.1074/jbc.m601966200
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Expression and Function of 51 Sarco(endo)plasmic Reticulum Ca2+-ATPase Mutants Associated with Darier Disease

Abstract: We examined possible defects of sarco(endo)plasmic reticulum Ca catalyze Ca 2ϩ transport coupled with ATP hydrolysis (Fig. 1) and play an essential role in maintaining Ca 2ϩ homeostasis in the cytoplasm and endoplasmic reticulum lumen of cells (1-7). SERCAs have three cytoplasmic domains: phosphorylation (P), nucleotide binding (N), and actuator (A) and 10 transmembrane helices (M1-M10 or 11 in the SERCA2b isoform, M11). In the Ca 2ϩ transport cycle, the ATPase is activated by the binding of two Ca 2ϩ ions fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 79 publications
3
47
0
2
Order By: Relevance
“…The potential role of Ca 2+ in the growth and differentiation of epithelial cells as well as keratinocytes is recognized [3,5,30]. Interestingly, the majority of SERCA2 mutations associated with classical DD reveal a reduction in the expression and activity of the pump [15][16][17][18][19][20]. Hence, an imbalance in cellular Ca 2+ signaling is an obvious readout of DD.…”
Section: Darier's Disease and Ca 2+ Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential role of Ca 2+ in the growth and differentiation of epithelial cells as well as keratinocytes is recognized [3,5,30]. Interestingly, the majority of SERCA2 mutations associated with classical DD reveal a reduction in the expression and activity of the pump [15][16][17][18][19][20]. Hence, an imbalance in cellular Ca 2+ signaling is an obvious readout of DD.…”
Section: Darier's Disease and Ca 2+ Signalingmentioning
confidence: 99%
“…Since the identification of the gene responsible for DD, about 140 different mutations of SERCA2 have been evaluated with different degrees of phenotypic severity associated with the levels of expression and function of the pump. However, mutations rendering a state of SERCA2 haploinsufficiency are congruent with the classical DD phenotype [12,[15][16][17][18][19][20].…”
Section: Genetics Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…2). The Darier disease-causing mutations of Ser 186 of SERCA2b, S186P and S186F also alter the kinetics of the EP processing and its impor-* This work was supported by a grant-in-aid for scientific research (B) ( tance as the residue in the immediate vicinity of TGES 184 has been pointed out (30,31). Notably also, Glu 439 is situated near the adenine binding pocket and its importance in the ATP binding and ATP-induced structural change have been shown (32,33 …”
Section: Sarcoplasmic Reticulum Camentioning
confidence: 99%
“…In vitro studies using Darier keratinocytes showed a decreased ER Ca 2 ϩ concentration (Dode et al, 2003;Foggia et al, 2006;Miyauchi et al, 2006;Pani et al, 2006). Upon Ca 2 ϩ depletion, misfolded proteins accumulated in the ER leading to induction of the unfolded protein response (UPR; Yoshida, 2007).…”
Section: Darier ' S Diseasementioning
confidence: 99%